PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA GURU SMKN 4 KLATEN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Sarbin . (STIE AUB Surakarta, 2014)
The aim of this study is investigate influence of leadership, communication, and job satisfaction to teacher performance of the Government Vocational High School 4 at Klaten. The Hypothesizing which have been formulated in this research is: there is direct and indirect influence of leadership, communication across job satisfaction to teacher performance of the Government Vocational High School 4 at Klaten. The research is a survey to teacher performance the Government Vocational High School 4 at Klaten Data have been collected with quesionary was processed with, validity and reliability test, the path analysis, t test, F test and test of R2. The t test have been done show that there is influence of leadership, communication, and job satisfaction to teacher performance the Government Vocational High School 4 at Klaten. The F test have been done show that there is influence of leadership, communication, and job satisfaction to teacher performance the Government Vocational High School 4 at Klaten as simultance. Keyword: leadership, communication, job satisfaction,performance.